Antimicrobial activities of a proline-rich proprotein from Spodoptera litura. (October 2018) - Yang, Li-Ling; Zhan, Ming-Yue; Zhuo, Yu-Li; Pan, Yue-Min; Xu, Yang; Zhou, Xiu-Hong; Yang, Pei-Jin; Liu, Hong-Li; Liang, Zi-Hao; Huang, Xiao-Dan; Yu, Xiao-Qiang; Rao, Xiang-Jun
Abstract: Antimicrobial peptides (AMPs) are produced by the stimulated humoral immune system. Most mature AMPs contain less than 50 amino acid residues. Some of them are generated from proproteins upon microbial challenges. Here, we report the antimicrobial activities of a proline-rich proprotein, named SlLebocin1 (SlLeb1), from the tobacco cutworm Spodoptera litura . SlLebocin1 cDNA contains a 477-bp open reading frame (ORF). It is mainly expressed in hemocytes and the midgut in naïve larvae. The transcript level was significantly induced in hemocytes but repressed in the midgut and fat body by bacterial challenges. The proprotein contains 158 amino acids with 3 RXXR motifs that are characteristic of some Lepidopteral lebocin proproteins. Four peptides corresponding to the predicted processed fragments were synthesized chemically, and their antimicrobial activities against two Gram-negative and two Gram-positive bacterial strains were analyzed. The peptides showed differential antimicrobial activities. For Escherichia coli and Bacillus subtilis, only the C-terminal fragment (124–158) showed strong inhibitory effects. For Staphylococcus aureus, all peptides showed partial inhibitions. None of them inhibited Serratia marcescens . Bacterial morphologies were examined by the scanning electron microscopy and confocal laser scanning microscopy. The antimicrobial peptides either disrupted cellular membrane or inhibited cell division and caused elongated/enlarged morphologies. The results may provide ideas for designing novel antibiotics. Highlights: A lebocin proprotein from S. litura was characterized. Some synthetic peptides affected bacterial growth. Peptide-treated bacteria showed different morphologies.